Praktek Model Perilaku Konsumen Ramah Lingkungan Dari Perspektif Teori Perilaku Terencana - Anita Maulina; Nur Fitri Rahmawati; Yoka Mai Patria (Akademi Sekretari Manajemen Taruna Bakti, 2023)
The main problem in this study is green consumer behavior for buying green packaged food in Depok City. Depok was chosen as the research location because Depok is near city from Jakarta. The purpose and urgency of the research is to determine the green behavior of consumers in culinary-based small businesses so that they can develop policies to overcome environmental problems by utilizing local wisdom of Depok City. The approach study is a quantitative approach using structural equation modeling. There are 120 consumers who are determined by purposive sampling technique. The results of data analysis concluded that subjective norms have a strong and significant influence on the purchase intention of buying green packaged food. In addition, the variables of attitude, subjective norm and perceived behavioral control have an effect of 78% on the intention to buy green packaged food in Depok City. Some conclusions and suggestions are described at the end of the paragraph. It is hoped that the written suggestions can provide input to the Depok city government to make Depok a Zero Waste city.